Questionário Para Avaliação Do Perfil Socio-Financeiro No Atendimento Oftalmológico Em Um Serviço Universitário - Brigagao, Cleide [UNIFESP] (2017)
Background: Vision impairment is one of the most serious disabilities that can happen to a person, because it brings social and individual negative impact. Even thus, the economic difficulties related to transportation fees, loss of the working day, as well as the lack of access to the services can lead to delay in ocular treatment. Studies can help to demonstrate the difficulties faced and so bring information for the improvement of care of patients to the specialist services. Purpose: To develop and apply a questionnaire for assessing the socioeconomic profile, as well as epidemiological data, adherence to treatment and the perception of the ophthalmic service quality provide for outpatients of the public healthcare system patients conducted by Department of Ophthalmology and Visual Sciences of the Federal University of São Paulo. Methods: Structured questionnaire with 23 questions was developed and applied to outpatients over 18 years, with more than 3 months of treatment, in the period from March-August 2016. The issues have been grouped according to the sociodemographic characteristics, access and transportation to the site of ocular assistance, expenses assistence, acquisition of eye care medicines and treatment adherence, satisfaction regarding Ophthalmology received. Results: A group of 211 respondents were interviewed (mean age= 54.0± 18; range 18.0-87 yrs. Hundred-two (48.3%) were male and 109 (51.7%) female. A total of 88.6% had family income of up to than R$ 2000,00 (less 2.3 minimum wages). Degree of schooling: 11.4% had no formal education, 33.2% had completed the elementary school I, 13.7% had elementary school II complete, 32.8% had high school complete 8.0% had college degree 0.9% were postgraduate. Of those surveyed, 62% had transportation fees, 68.7% had spent with food outside of home and 53.6% with medicines or inputs. Regarding their satisfaction with services medical received 93.8% considered great or good. Conclusion: It is a needy population, has a low-level education and depends on specialized public health services. This project has had a positive impact within these community because it provides health care to this public and for the professional master's student learning how to develop and apply a specific questionnaire for this purpose, the patients declared to be very satisfied with the ocular attendance Ophthalmology Department and Visual Sciences at the Federal University of São Paulo.